The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12889-021-11254-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use among children under five years with diarrhea in rural communities of Gulu, northern Uganda: a cross-sectional study

Abstract: Background Diarrhea is the second leading cause of mortality in children under 5 years of age globally, and the risk of death increases with practices such as restriction of fluid intake and inappropriate use of antibiotics. We determined the prevalence of antibiotic use in managing diarrhea in children under 5 years of age in rural communities of Gulu district, northern Uganda. Method A cross-sectional study among children under 5 years with diarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The risk of bias was judged as of low level for the 26 studies we included [20, 21, 23-25, 38-42, 44-48, 51, 52, 54, 57, 59, 61-63, 66, 67, 69]. It was moderate (i.e., some concerns) and high levels in 11 [22,43,50,53,55,56,58,60,64,65,70] and two [49,68] of the remaining studies, respectively. Most studies had a low or moderate risk of participant selection bias, while this was of a high level in nine studies [20, 21, 23, 49, 52, 58, 62, [53,55,56,60,64,68,69,71].…”
Section: Risk Of Bias Of the Included Studiesmentioning
confidence: 99%
“…The risk of bias was judged as of low level for the 26 studies we included [20, 21, 23-25, 38-42, 44-48, 51, 52, 54, 57, 59, 61-63, 66, 67, 69]. It was moderate (i.e., some concerns) and high levels in 11 [22,43,50,53,55,56,58,60,64,65,70] and two [49,68] of the remaining studies, respectively. Most studies had a low or moderate risk of participant selection bias, while this was of a high level in nine studies [20, 21, 23, 49, 52, 58, 62, [53,55,56,60,64,68,69,71].…”
Section: Risk Of Bias Of the Included Studiesmentioning
confidence: 99%
“…Recent efforts to measure antibiotic use in sub-Saharan African hospitals have been documented [ 19 , 20 , 21 , 22 ]. However, there are limited studies that utilize the standardized WHO PPS methodology for resource-limited settings, such as Ugandan hospitals [ 23 , 24 , 25 ]. This paper presents data from 13 hospitals in the context of a global health security agenda project for strengthening antimicrobial stewardship programs in low- and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“… 28–30 Studies have shown that diarrhea is a major concern in sub-Saharan Africa and Uganda in particular. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%